(untitled) (قضايا سياسية, 2025)
The age of the global transformations witnessed by the international system after the Cold War, the focus on the interpretation of international relations is no longer focused on the role of States. The functions of transnational networks, especially international non-governmental organizations, have been activated through various structures and processes that can coordinate interests and needs. It creates new opportunities and activities on the global level. It works to activate new global issues such as protecting human rights, environmental and relief issues, health, democratic transformation, empowering marginalized communities and other issues. These cross-border issues must take the lead The agenda of the Global Agenda, which is no longer limited to the State only, but extends to the concerns of various non-state actors, as it necessitates the creation of positive cooperation in partnership with various actors, especially international non-governmental organizations, which have committed themselves to express the international human conscience By intervening in international and domestic issues, supported by the emergence of trends in international relations that consider that the idea of ​​absolute sovereignty of the state is no longer acceptable, but the intervention of the international community in some things that were in the past considered an internal matter that some consider necessary and obligatory, Payment of payment International non-governmental organizations to play an important role in world politics, especially after the failure of the international system based on the State and on intergovernmental organizations.